PHRASEOLOGICAL UNITS AS LINGUISTIC AND CULTURAL UNITS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article explores phraseological units as integral components of language and culture, highlighting their dual role in reflecting linguistic systems and cultural identities. By examining examples from different languages, the study delves into the semantic, structural, and cultural characteristics of phraseological units, showcasing their significance in fostering cross-cultural understanding.